KORELASI GREEN INOVATION, CARBON EMISSION DISCLOSURE, ECO-EFFICIENCY: IMPLIKASI NILAI PERUSAHAAN - Siregar, Nolita Yeni; Yolanudin, Riska Nanda; Meiliana, Reva; Ramadhaniyah, Rieka (Jurnal Riset Terapan Akuntansi, 2024)
This study aims to empirically examine whether green innovation, carbon emission disclosure, and eco-efficiency affect firm value. The study covers the period from 2020 to 2022, with a sample of 21 energy companies listed on the Indonesia Stock Exchange (IDX). The data used in this research is secondary data, and the sample was selected using purposive sampling based on specific criteria, resulting in 63 samples. The analysis techniques applied include descriptive statistical analysis and multiple regression analysis, using Eviews version 12. The hypothesis testing results indicate that green innovation and carbon emission disclosure have no effect on firm value, while eco-efficiency has a significant effect on firm value..Keywords: Green Innovation ,Carbon Emission Disclosure, Eco-efficiency, and firm value